Strategi Pengambangan Objek Wisata Terpadu Kabupaten Timor Tengah Selatan - Selvianus Imanuel Kause; Apriana H.J. Fanggidae; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out strategies for developing integrated tourist attractions in South Central Timor Regency so that they can increase tourist attraction and also find out what components are needed in developing tourist attractions in South Central Timor Regency using SWOT analysis. This research use desciptive qualitative approach. The data collection techniques used were interviews, observation and documentation. The results of the research determine the policies that should be prioritized by the government in efforts to develop integrated tourist attractions in South Central Timor district. This research shows that there is a need to increase human resources in developing tourist attractions, improving infrastructure, supporting infrastructure, then the main focus in this research based on the concept of integrated tourism is the Tour Package program that has been launched which would be very good if it received more attention.